Soil quality indicators in irrigated sugarcane crops - Almeida, Letícia Silva; Ferreira, Verônica Aparecida Santos; Fernandes, Luiz Arnaldo; Frazão, Leidivan Almeida; Oliveira, Agda Loureiro Gonçalves; Sampaio, Regynaldo Arruda (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the effects of land use change on the dynamics of organic carbon, on total nitrogen, and on microbial soil properties over time, in irrigated sugarcane crops. The systems were evaluated in four areas with sugarcane in a chronosequence of 5, 7, 8, and 9 years of cultivation, besides a native vegetation area. The soil samples were analyzed for C and N stocks, and for the microbiological properties of the soil. The system with 8 years showed the highest C values of microbial biomass and basal respiration, and the lowest ones for microbial metabolic quotient (qCO2). The highest values of C and N stocks were observed in the native vegetation area. These results are associated with the constant deposition of litter and intense biological activity in the native vegetation. The deposition of sugarcane straw on the soil surface, over time, improved soil quality and kept the soil stocks of C and N similar to those observed in the native vegetation area.